Key concepts in teaching primary mathematics - Haylock, Derek (SAGE key concepts., 2007)
Covering the key principles and concepts in the teaching and learning of mathematics in elementary schools, this text provides trainee and practicing teachers with a quick and easy reference to what they need to know for their course, and in the classroom.